2008
DOI: 10.1007/s10681-008-9768-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, sensorial and genomic profiling of traditional Italian tomato varieties

Abstract: Fruit Xavour of traditional tomato ecotypes diVers from that of modern varieties, the latter being often blamed for lack of Xavour. To respond to consumer complaints breeders should know the range of genetic variability available in tomato resources, including local ecotypes, for improving Xavour. For this purpose, multitrait characterization, including biochemical, sensorial and molecular analyses, was performed on 12 Italian tomato ecotypes that belong to diVerent types (San Marzano, Sorrento, and Vesuvio). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
(34 reference statements)
7
22
0
Order By: Relevance
“…Likewise, the sugar content in Penjar is clearly higher than in other tomato landraces from the Mediterranean basin (Ercolano et al, 2008;Loiudice et al, 1995). The high sugar concentrations of some accessions could be related to their low fruit weight (mean 64.1 g).…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, the sugar content in Penjar is clearly higher than in other tomato landraces from the Mediterranean basin (Ercolano et al, 2008;Loiudice et al, 1995). The high sugar concentrations of some accessions could be related to their low fruit weight (mean 64.1 g).…”
Section: Discussionmentioning
confidence: 86%
“…The molecules influencing these features have different chemical-physical characteristics and might change the sensorial perception. For example, Pratta et al (2011) found levels ranging between 3.79 and 6.61 (°Brix) in sixteen analysed recombinant inbred lines, whereas Ercolano et al (2008) measured from 4.10 to 5.50°Brix in a group of 16 Italian ecotypes. In particular, sweetness and sourness are related to the sugar and acid contents, respectively, and they also contribute to the overall aroma (Causse et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After processing, they also showed a cytotoxic effect towards cancer cells, thus revealing their potential use for the production of tomato-based functional foods. This ecotype has been previously characterised at morphological, biochemical, molecular (Ercolano et al, 2008) and sensorial levels (Carli et al, 2011), and therefore, it constitutes a good control for evaluating the organoleptic qualities of the three yellow genotypes that exhibit a similar fruit typology. The yellow fruit genotypes were compared with the red fruit ecotype Ves2001 (E48), which represents a traditional Italian fruit typology (the Vesuvio type) and is characterised by a particular flavour and taste due to its genomic constitution and cultivation in a volcanic area (Carli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be the case of the varieties "De la pera" and "Muchamiel" among others from Spain (Brugarolas et al, 2009), "San Marzano", "Sorrento" and "Vesubio" or "Abruzzese" among others from Italy (Ercolano et al, 2008;Mazzucato et al, 2010) or "Santorini" and "Pastra" among others from Greece (Terzopoulos and Bebeli, 2010). In general, a high level of variation has been described in tomato landraces.…”
Section: Discussionmentioning
confidence: 99%